Sri Lanka's vernacular press and the peace process - Nadarajah, Suthaharan; Asia Foundation (Colombo : Asia Foundation, 2005)
Study funded by various intergovernmental and international agencies.
Keywords: Peace-building -- Press coverage -- Sri Lanka; Ethnic press -- Political aspects -- Sri Lanka; Sri Lanka -- Politics and government -- 21st century -- Press coverage